Five Roads That Converge at the Cyclic Peroxy-Criegee Intermediates: BF3‑Catalyzed Synthesis of β‑Hydroperoxy-β-peroxylactones - Vil’, Vera A; Gomes, Gabriel dos Passos; Ekimova, Maria V; Lyssenko, Konstantin A; Syroeshkin, Mikhail A; Nikishin, Gennady I; Alabugin, Igor V; Terent’ev, Alexander O (Journal of organic chemistry, 2018)
We have discovered synthetic access to β-hydroperoxy-β-peroxylactones via BF3-catalyzed cyclizations of a variety of acyclic precursors, β-ketoesters and their silyl enol ethers, alkyl enol ethers, enol acetates, and cyclic acetals, with H2O2. Strikingly, independent of the choice of starting material, these reactions converge at the same β-hydroperoxy-β-peroxylactone products, i.e., the peroxy analogues of the previously elusive cyclic Criegee intermediate of the Baeyer–Villiger reaction. Computed thermodynamic parameters for the formation of the β-hydroperoxy-β-peroxylactones from silyl enol ethers, enol acetates, and cyclic acetals confirm that the β-peroxylactones indeed correspond to a deep energy minimum that connects a variety of the interconverting oxygen-rich species at this combined potential energy surface. The target β-hydroperoxy-β-peroxylactones were synthesized from β-ketoesters, and their silyl enol ethers, alkyl enol ethers, enol acetates, and cyclic acetals were obtained in 30–96% yields. These reactions proceed under mild conditions and open synthetic access to a broad selection of β-hydroperoxy-β-peroxylactones that are formed selectively even in those cases when alternative oxidation pathways can be expected. These β-peroxylactones are stable and can be useful for further synthetic transformations.